A green approach to porous and dense antifouling membranes through solvent-free bulk polymerization. (2nd October 2015) - Zhang, Runnan; Peng, Jinming; Su, Yanlei; Fan, Xiaochen; Jiang, Zhongyi; Zhao, Xueting; Liu, Jiazhen; Li, Yafei; Zhao, Jiaojiao
Abstract: In this study, a green approach to prepare both porous and dense antifouling membranes was developed through solvent-free bulk polymerization of the casting solution containing 2-hydroxyethyl methacrylate (HEMA) and pre-dispersed silica nanoparticles in two glass sheets under pressure. Porous polyHEMA membranes were prepared via removing the silica nanoparticles embedded in the polymer matrix. Dense poly(HEMA/MAA)/SiO2 membranes were fabricated by adding methacrylic acid (MAA) as co-monomer without removing the silica nanoparticles. Membrane thickness could be conveniently controlled by varying the distance between the two slide glasses. Field emission scanning electron microscope (SEM), X-ray photoelectron spectroscopy (XPS) and water contact angle measurement were employed to characterize the morphology and surface chemical composition of the resultant membranes. The porous polyHEMA membranes exhibited high efficiency in purification of bovine serum albumin (BSA) from BSA/yeast solution while the dense poly(HEMA/MAA)/SiO2 membranes exhibited high rejection of orange GII. Both porous membranes and dense membranes exhibited strong hydrophilicity as a result of hydrophilic monomer HEMA, leading to good antifouling properties. Highlights: A solvent-free approach to fabricate dense and porous membranes was developed. The membrane pores can be controlled by the size of silica nanoparticles. The membranes exhibited high antifouling and separation performance.